2018
DOI: 10.15406/jpcpy.2018.09.00512
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Psychological Vaccination for Potentially Traumatized Children

Abstract: Objectives: Traumatic events and associated stress due to ongoing war and displacement may have severe adverse effects on psychosocial development of children. Although more than half of traumatized children are expected to develop posttraumatic psychopathology, no effective prevention has been found. The present study aims to investigate if Crisis Intervention Program for Child and Adolescents (CIPCA) has protective effects on mental wellbeing of child survivors of the ISIS war and displacement in the Kurdist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A WHO survey confirms that the first onset of mental disorders usually occurs before the age of 14 years 13,14 [15][16][17] . A pilot study showed low psychological symptom scores at one-year and two-year follow-up 17 .…”
Section: Preventing Posttraumatic Psychopathologymentioning
confidence: 99%
“…A WHO survey confirms that the first onset of mental disorders usually occurs before the age of 14 years 13,14 [15][16][17] . A pilot study showed low psychological symptom scores at one-year and two-year follow-up 17 .…”
Section: Preventing Posttraumatic Psychopathologymentioning
confidence: 99%
“…For instance, social activities which are a core part of school training (e.g. playing, art, dance lessons, singing and others) might support the psychosocial development of children which may have benefits on mental well-being and, could also contribute the psychosocial development 7,14 . However only one out of three school-age refugee children could attend school in Turkey 9 .…”
Section: Introductionmentioning
confidence: 99%